Evaluation of Taxonomy of User Intention and Benefits of Visualization for Financial and Accounting Data Analysis - Savoska, Snezana; Loshkovska, Suzana (My University, 2013)
In this paper we evaluate the taxonomy model for multidimensional data visualization for accounting data analysis. This taxonomy takes into consideration users’ intentions and also, the benefits of visualization for analysts, businessmen and managers who use financial and accounting data. We also explain the proposed taxonomy as well as the taxonomic framework which contains three groups of attributes. They are classified according to visual techniques and their capabilities. We have analyzed several multidimensional and multivariate visualization techniques, each presented in a table according to the proposed taxonomy. This table will determine their capability and capacity to solve specific visual problems. Evaluation of this taxonomic model for visualization of multidimensional and multivariate financial or accounting data implies the possibility for introducing an automatic selection of a visualization techniques and the best visual representation.
Keywords: data visualization, taxonomy evaluation, financial and accounting data, multidimensionality